2020
DOI: 10.1111/febs.15350
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the early stages of peptide formation during the biosynthesis of teicoplanin and related glycopeptide antibiotics

Abstract: The biosynthesis of the glycopeptide antibiotics (GPAs) demonstrates the exceptional ability of nonribosomal peptide (NRP) synthesis to generate diverse and complex structures from an expanded array of amino acid precursors. Whilst the heptapeptide cores of GPAs share a conserved C terminus, including the aromatic residues involved cross-linking and that are essential for the antibiotic activity of GPAs, most structural diversity is found within the N terminus of the peptide. Furthermore, the origin of the (D)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 68 publications
3
38
0
Order By: Relevance
“…37,38 The utility of this approach is not limited by the requirement to maintain E-domain activity, as C-domains are not always exclusively active on the correct peptide stereochemistry as seen previously for teicoplanin M3 and M7, for example. 14,25 Having seen the importance of E-domains within modular exchange strategies, we also tested domain exchange experiments investigating the linkers with the E-domains found in the M4 and M5 modules from the Tcp11 protein. Here, we demonstrated that the construct possessing the C-E domain inter-modular linker (IML) connecting M4 with M5 retains activity but not one with the IML connecting M5 with M6.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…37,38 The utility of this approach is not limited by the requirement to maintain E-domain activity, as C-domains are not always exclusively active on the correct peptide stereochemistry as seen previously for teicoplanin M3 and M7, for example. 14,25 Having seen the importance of E-domains within modular exchange strategies, we also tested domain exchange experiments investigating the linkers with the E-domains found in the M4 and M5 modules from the Tcp11 protein. Here, we demonstrated that the construct possessing the C-E domain inter-modular linker (IML) connecting M4 with M5 retains activity but not one with the IML connecting M5 with M6.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst in the context of the M5-6 + M3a + M4 pathway this could possibly be explained by other as yet unidentied intermodule interactions, in the experiments where synthetic tripeptide was loaded on M3 and incubated with M5 the evidence for N-terminal extension appears unambiguous. Whilst unexpected, it should be noted that there is a general lack of structural information concerning the presentation of acceptor substrates within Cdomains, 5,41,[43][44][45] and that coupled with the reported exibility of the NRPS assembly line (even within fused modules), 25,41,42,46 there is no evidence that the attack of an acceptor peptide onto a donor amino acid is explicitly prevented. This intriguing result highlights the importance of obtaining further structural snapshots of the NRPS C-domain in relevant catalytic states, and is further underlined by the diverse range of catalytic activities performed by domains derived from Cdomains.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have demonstrated a role for these proteins as chaperones in the NRPS assembly line. In these reports, the soluble production of one or more NRPS A-domains in Escherichia coli was shown to be reduced or abolished in the absence of the MLP that is from the same biosynthetic pathway as the NRPS, suggesting that the MLP (called the cognate MLP) is required for the proper folding of the A-domain protein ( Imker et al, 2010 ; Boll et al, 2011 ; McMahon et al, 2012 ; Zolova and Garneau-Tsodikova, 2012 , 2014 ; Kaniusaite et al, 2020 ). Additionally, some MLPs have been shown to influence amino acid activation by the corresponding NRPS.…”
Section: Introductionmentioning
confidence: 99%